2021
DOI: 10.1088/2515-7639/abca7b
|View full text |Cite
|
Sign up to set email alerts
|

Modeling process–structure–property relationships in metal additive manufacturing: a review on physics-driven versus data-driven approaches

Abstract: Metal additive manufacturing (AM) presents advantages such as increased complexity for a lower part cost and part consolidation compared to traditional manufacturing. The multiscale, multiphase AM processes have been shown to produce parts with non-homogeneous microstructures, leading to variability in the mechanical properties based on complex process–structure–property (p-s-p) relationships. However, the wide range of processing parameters in additive machines presents a challenge in solely experimentally un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 107 publications
1
26
0
Order By: Relevance
“…k=1 ⊆ R 2 is the input trajectory, f lm is the RK4 approximation of the linear model (9), with identified matrices C and D, T k is the transformation matrix between global and local coordinates in (10), µ k is the discretized maximum allowed deviation from the target geometry, W are the limits of the working space of the device, v max is the maximum allowable speed, and a max is the acceleration limit.…”
Section: A First-stage Optimization Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…k=1 ⊆ R 2 is the input trajectory, f lm is the RK4 approximation of the linear model (9), with identified matrices C and D, T k is the transformation matrix between global and local coordinates in (10), µ k is the discretized maximum allowed deviation from the target geometry, W are the limits of the working space of the device, v max is the maximum allowable speed, and a max is the acceleration limit.…”
Section: A First-stage Optimization Formulationmentioning
confidence: 99%
“…These design principles are motivated by the requirements of "Industry 4.0" where machines are no longer standalone setups and are instead connected in a network, making data more easily available [8]. This data can be exploited to improve performance; for example, it can be leveraged to create data-driven models, avoiding the labour intensive process of developing and maintaining first principles based ones [9]. Future manufacturing is also expected to be more distributed and personalized (e.g., "Manufacturing as a service") [10], [11], leading to smaller volumes for any given part, possibly produced across a pool of non-homogeneous machines.…”
Section: Introductionmentioning
confidence: 99%
“…Because the LPBF forming process is complex with several influencing factors, it is challenging to conduct research and analyses based on physical models. However, the data-driven approach has the advantage of modeling complex physical problems [10], and some classical machine learning models, such as support vector machines and linear regression algorithms, have been used for the classification and prediction of forming quality in additive manufacturing [11]. An important challenge of data-driven approaches for quality prediction is the accuracy and speed of prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have investigated the mechanical properties of SLM Invar and suggested process parameters to achieve a stable and refined microstructure with comparable mechanical properties to the traditionally fabricated alloy [ 22 ]. Powder-bed AM processes, like SLM, can produce high-resolution parts, but the build volumes of these systems are typically less than 0.3 m 3 [ 23 ]. Additionally, powder feedstock is very expensive, so these processes are not ideal for building large-volume components (such as molds and dies) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%